Role Mechanical-build department of the Kiev branch of the Russian Technical Society in research in the field of railway - Grytsiuta, O. O. (History of science and technology, 2016)
The article highlights the process of becoming scientific centers of research in the field of railway science in Ukraine in the second half of Nineteenth century.Based on a thorough study of documents and literature managed to identify major centers of research in this area. A special role in the compiling scientific centers belongs voluntary union of scientists. Important place among these take the branch of the Russian Technical Society, the most active was the Kiev branch of the Russian Technical Society, on which base successfully operated Mechanical-build department.